2010
DOI: 10.1645/ge-2296.1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Vertical Transmission of Two Genotypically and Geographically Diverse Isolates of Trypanosoma cruzi in Mice

Abstract: Although principally considered a vector-borne disease, the vertical transmission of Trypanosoma cruzi from mother to child is now recognized as a significant and increasing threat to human health. Despite its importance, significant gaps exist in our understanding of the relationships between genotype, virulence, and the extent of vertical transmission of this pathogen. To better understand these relationships, we describe the comparison of a South American-derived Type I isolate (BS) of T. cruzi to a Type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(31 reference statements)
4
13
0
Order By: Relevance
“…However, if we suppose that rats are more like the lab mice in [18] than like raccoons, strain 2 can win in the woodrat cycle as well. For the given values, if we assume that p 2W ≥ 0.25 (hence p w max ≥ 0.375 as in Table 2), then strain 2 wins if adapted to oral transmission, and for higher values of p 2W (e.g.…”
Section: Trade-off and Competitionmentioning
confidence: 99%
“…However, if we suppose that rats are more like the lab mice in [18] than like raccoons, strain 2 can win in the woodrat cycle as well. For the given values, if we assume that p 2W ≥ 0.25 (hence p w max ≥ 0.375 as in Table 2), then strain 2 wins if adapted to oral transmission, and for higher values of p 2W (e.g.…”
Section: Trade-off and Competitionmentioning
confidence: 99%
“…If we use the data on the probability of vertical transmission in mice of [23], i.e., p 1 = 1/3 and p 2 = 2/3, and the estimates of the probability of oral transmission of [10], and assume that T. cruzi I and IIa are equally transmitted via this pathway, i.e., ρ 1 = ρ 2 = 0.177 host/vector, the condition A < β h1 < B for Q to affect the outcome of the competition between the two strains (see section 3.1) becomes: 2 β h2 + 0.177 H < β h1 < 2 β h2 + 0.177 H Q v /Q h when Q h < Q v and 2 β h2 + 0.177 H Q v /Q h < β h1 < 2 β h2 + 0.177 H when Q h < Q v . Even if no precise data is available for the maximum rate at which hosts consume vectors in the field, H, the consumption of one vector per host and per year has been shown numerically to be sufficient to account for the observed T.cruzi prevalences in the SE US [13].…”
Section: Fit With Available Datamentioning
confidence: 99%
“…Vertical transmission has been reported among placental hosts such as rats and mice [22,23], and humans [24]. In addition, sylvatic hosts such as raccoons and opossums are opportunistic feeders whose diet includes insects, and experimental studies have shown that they can get infected by ingesting infected vectors [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Texas and northern Mexico, meanwhile, both strains are found at roughly equal levels in woodrats (Neotoma micropus) [4]. T. cruzi I is often described as chagasic and more virulent (see, e.g., [19]) compared to T. cruzi IV, which has been found to be better adapted to vertical transmission [11], and the importance of vertical and oral transmission in an epidemiological landscape where classical stercorarian transmission is disadvantaged almost surely plays a role in mediating interstrain competition here. Host-vector interactions-in particular, the two distinct contact processes that cause stercorarian and oral infection of hosts-add an extra layer to the epidemiological landscape, extending the framework of Levins to incorporate the densities of not only the parasite but also the hosts and vectors.…”
Section: Introductionmentioning
confidence: 99%